Population Dynamics of Freshwater Molluscs in the Lentic Eco – systems in and Around Chennai - M.B. Ragunathan2; M. Selvanayagam3, A. Johnpaul1* (Recent Research in Science and Technology, 2010)
A population dynamics study of freshwater molluscs in and around Chennai (Tamil Nadu, India) was conducted at ten locations which include Kovoor pond, Kunrathoor pond, Velachery Lake, Pallikkaranai Lake, Chengalpet Lake, Chembarambakkam Lake, Puzhal Lake, Chetpet pond, Paranur Lake and Porur Lake during November 2006 to March 2007. A total of seven species of freshwater molluscs belonging to four families that comprises of Viviparidae, Pilidae, Thiaridae and Planorbidae and six genera (Bellamya, Pila, Thiara, Sulcospira, Paludomus and Indoplanorbis) were found in the lentic eco-systems in and around Chennai and identified at the Zoological Survey of India, Southern Regional Station. Physico-chemical parameters like pH, temperature, dissolved oxygen, salinity, alkalinity and its variation at all the collection sites were analyzed. An analysis was also conducted to study the variation and impact of aquatic (freshwater) plants in the life cycle of gastropods. As the molluscs are intermediatory hosts between the parasites and animals, an overview study was also carried out on the known molluscs’ various parasites and their diseases. 1Unit of Pathobiology, Department of Zoology, University of Madras, Guindy Campus, Chennai-600025, India 2Zoological Survey of India, Southern Regional Station, Pattinapakkam, Chennai-600028, India 3Department of Advanced Zoology and Biotechnology, Loyola College, Chennai-600034, India